The Impact of Corporate Governance in Indonesia's Biggest Banks on Accounting Conservatism Through Audit Quality - Nurmansyah, Agung (Ilomata International Journal of Tax and Accounting, 2024)
Banks are typically linked with conservative accounting practises due to the handling of big assets. This study investigates how company governance impacts accounting conservatism by focusing on audit quality. The analysis involves the independent variable corporate governance, the intervening variable audit quality, and the dependent variable accounting conservatism. This study focused on the 10 largest banks in Indonesia that were listed on the Indonesian stock exchange from 2015 to 2020. Using purposive sampling, 9 banks were selected for the study. Data collection was conducted using secondary data, the statistical method used was path analysis. This study's findings suggest that corporate governance has a negative impact on audit quality and accounting conservatism. Corporate governance negatively affects audit quality and through audit quality affects accounting conservatism.